PEMBUATAN PUPUK KOMPOS CAIR DARI BUAH LIMBAH DI SENTRA PENJUALAN BUAH-BUAHAN DESA TEBAT MONOK KABUPATEN KEPAHIANG - Deselina .; Erniwati .; Bilman WS (Universitas Bengkulu, 2014)
Increasing the amount of waste to be balanced with the public's awareness of environmental commercialize clean and healthy. One way to reduce the amount of waste isby using fruit waste into liquid compost. Therefore, raw materials derived from the papayafruit, then the resulting compost is liquid compost flavored papaya. The purpose of thisDIPA fund service activities is increasing the skills of the youth in particular members ofyouth, housewives and members of the PKK on how to make liquid compost, can producegood quality liquid compost, improve understanding of the society about the importance ofhousehold waste management, and increase family income in the Village of Tebat MonokKepahiang District. Service activities are carried out by the method of education andtraining on the importance of waste management, utilization waste environment, and howmarketing the product waste, and training on knowledge of how to make liquid compostquality and composting demonstration of liquid and liquid compost application on crops.The results show that the devotion of liquid composting of fruit waste in the Fruits SalesCenter at Village Tebat Monok is one right step in processing the fast decaying fruit waste(papaya). This liquid composting, in addition to adding the fruit merchant skills inmanaging waste, businesses can also be used as an attempt to increase the income of thetraders in the village.Keywords: Liquid Compost, Waste, Sales